Evaluasi Kualitas Pelayanan Paket Wisata di Bukit Lawang - Tampubolon, Graceita Juliana (Politeknik Pariwisata Medan, 2024)
This study aims to evaluate Bukit Lawang tour packages through qualitative methods by distributing questionnaires directly to tourists. The main focus is to analyze the level of tourist satisfaction with tour packages and the performance of Bukit Lawang as a tourism destination. The evaluation results show that Bukit Lawang tour packages have managed to achieve a high level of satisfaction, with around 94% of tourists satisfied with their experience. Factors such as the level of satisfaction of the tourist experience are the main reasons for visiting again and the Bukit Lawang area is clean, beautiful and still maintained. In addition, Importance Performance Analysis (IPA) and Cartesius charts are used to evaluate the importance of these factors and the extent to which the tour package has met the expectations of tourists. The results of this analysis provide deep insight into the areas that need improvement in the development of tour packages. Although it has achieved a high level of satisfaction, this evaluation emphasizes the importance of continuous maintenance and improvement to maintain the attractiveness and quality of Bukit Lawang tour packages. This evaluation has an important impact in supporting the development and sustainability of tourism in Bukit Lawang.